Struktur Corporate Governance dan Financial Indicators terhadap Nilai Perusahaan (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Sri Rubitania Khoerunisa; Ade Imam Muslim (Universitas Katolik Indonesia Atma Jaya, 2021)
This research aims to determine the description of the structure of corporate governance, financial indicators and firm value in manufacturing companies, and to determine the effect of corporate governance structure and financial indicators on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 Period either simultaneously or Partial. This research is a type of quantitative research with the research method used is descriptive and verification methods. The population in this study were manufacturing companies listed on the IDX with a total sample of 42 companies which were determined by purposive sampling method. Data analysis used panel data regression analysis, classical assumption test, and hypothesis testing using the coefficient of determination analysis, F test, and t-test. Based on the results of panel data regression with a significance level of 5%, it can be concluded that the corporate governance structure and financial indicators have a significant effect on firm value simultaneously. Meanwhile, partially the corporate governance structure has no effect on firm value, while financial indicators have a positive and significant effect on firm value.